2016
DOI: 10.1111/maps.12727
|View full text |Cite
|
Sign up to set email alerts
|

Water in the Martian interior—The geodynamical perspective

Abstract: Petrological analysis of the Martian meteorites suggests that rheologically significant amounts of water are present in the Martian mantle. A bulk mantle water content of at least a few tens of ppm is thus expected to be present despite the potentially efficient degassing during accretion, magma ocean solidification, and subsequent volcanism. We examine the dynamical consequences of different thermochemical evolution scenarios testing whether they can lead to the formation and preservation of mantle reservoirs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 245 publications
(511 reference statements)
0
19
0
Order By: Relevance
“…Considering a dry mantle and dry crustal rheology also provides a good fit to the three T e constraints. By using crustal models similar to our UCM case, Breuer et al (2016) and Grott and Breuer (2008) found that a dry mantle and dry crustal rheology is not in agreement with the Noachian low T e . Indeed, a dry crust is stronger and the thinner incompetent bottom crustal layer disappears earlier both in the north and in the south in Mars evolution.…”
Section: Discussionmentioning
confidence: 68%
“…Considering a dry mantle and dry crustal rheology also provides a good fit to the three T e constraints. By using crustal models similar to our UCM case, Breuer et al (2016) and Grott and Breuer (2008) found that a dry mantle and dry crustal rheology is not in agreement with the Noachian low T e . Indeed, a dry crust is stronger and the thinner incompetent bottom crustal layer disappears earlier both in the north and in the south in Mars evolution.…”
Section: Discussionmentioning
confidence: 68%
“…This can be regarded as an addition of dense materials, such as magmatic intrusions in the crust. For L <0, a negative density contrast is defined to reside in the upper mantle at 150‐km depth, where the largest amount of melting is expected (Breuer et al, ). This can represent either a positive temperature anomaly or a depleted layer resulting from the prior extraction of magma in the upper mantle.…”
Section: Modelingmentioning
confidence: 99%
“…Modelers often assume equilibrium crystallization of the magma ocean after accretion so whole-mantle convection begins immediately after solidification (Breuer et al, 2016). In contrast, fractional crystallization of the magma ocean would produce a gravitationally unstable configuration that overturns in <100 Myr via Rayleigh-Taylor instability (Elkins-Tanton, 2008;Elkins-Tanton et al, 2003, 2005.…”
Section: Plausibility Of Delayed Hydrogenationmentioning
confidence: 99%
“…Hydrous melting promotes efficient degassing of water from the upper mantle as proto-Mars grows, but the lower mantle may remain unmelted (Médard & Grove, 2006;Pommier et al, 2012). The water content of the upper mantle is~200 ppm according to measurements of water in apatite inclusions from basaltic shergottites (Breuer et al, 2016;Taylor, 2013). The saturation limit of olivine is only a few times higher at~1,000 ppm.…”
Section: Introductionmentioning
confidence: 99%